Teaching English in Early Childhood Education: a Description of the Pedagogical Practice Adopted in the Municipality of Southern Brazil - Bortolotti, Fernanda Seidel; Krause-Lemke, Cibele (Educational Challenges, 2021)
The purpose of this study is to investigate teaching English in Early Childhood Education (ECE) in a municipality of southern Brazil. The country has not agreed to make English language teaching compulsory for this age, but some private schools have introduced English language teaching on the premises . Regarding methodology, the experimental study was conducted in schools “A” and “B”. Private school “A” was represented by a teacher with her group of four-year-old children. State school “B” was attended by two representatives of the volunteer program who worked with a group of five-year-olds. The research tools were observation in the classroom from each group, questionnaires answered by the teacher and volunteers, individual interviews with each of them, and a documentary analysis of the pedagogical project of schools, pedagogical materials. The experiment was conducted in compliance with all ethical standards. The analysis resulted in an understanding of the importance of such aspects as: duration and frequency of classes, the number of groups, lack of books for students and teachers, limited use of English by teachers and students; and the predominance of listening/speaking among other students’ skills in both schools. The teacher and the volunteers jointly acknowledged this advantage, noting that different techniques were used. Each group of teachers tried to improve the learning process, taking into account the preferences of the students. The volunteers of school “B” followed the structured plan of the lesson according to the program, used various types of activities. In school “A” the teacher used one type of activity at the lesson. Although the group had four-year-old children, it did not have significant negative consequences. According to the results of the study, it can be concluded that the approach proposed by the teachers is based on teaching English as a foreign language (EFL). The development of language education in Brazil has a long way , given the establishment of public policy on еarly сhildhood еducation system in combination with theoretical and practical researches used in the educational process.